Auditor characteristics and the issuance of going concern opinion - Osman, Mohammad Noor Hisham; Turmin, Siti Zaidah; Muhamad, Haslinah; Hussain, Rasyiqah (Medwell Journals, 2016)
Auditor should issue Going Concern audit opinion (GC opinion) when there is doubt about the ability of client to continue operation in the next one year, according to International Standard on Auditing 570 (ISA 570). However, in the context of Malaysia auditors tend to issue GC opinion to a small number of financially distress companies only. This situation motivates this study to investigate the effect of three auditor characteristics namely specialization, switching and remuneration on the possibility of GC opinion issuance. The study found significant positive relationship between the amount of auditor remuneration and the issuance of GC opinion. This might be due to operational aspect of auditing as before auditors issue any non-unqualified opinion report they have to conduct additional substantive test, documentation and discussion and negotiation with clients.